1999
DOI: 10.1128/mcb.19.8.5800
|View full text |Cite
|
Sign up to set email alerts
|

Akt/Protein Kinase B Inhibits Cell Death by Preventing the Release of Cytochrome c from Mitochondria

Abstract: Growth factors signaling through the phosphoinositide 3-kinase/Akt pathway promote cell survival. The mechanism by which the serine/threonine kinase Akt prevents cell death remains unclear. We have previously shown that Akt inhibits the activity of DEVD-targeted caspases without changing the steady-state levels of Bcl-2 and Bcl-x L . Here we show that Akt inhibits apoptosis and the processing of procaspases to their active forms by delaying mitochondrial changes in a caspase-independent manner. Akt activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
437
6
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 604 publications
(470 citation statements)
references
References 43 publications
25
437
6
2
Order By: Relevance
“…In fact, it enhances glucose uptake by stimulating the expression of the plasma membrane glucose transporter Glut-1, 18 and it mediates the activation of 6-phosphofructo-2-kinase 19 and hexokinase. 20 Thus, PKB/Akt activation may favor cell survival, 21,22 or alternatively it may support execution of the final apoptotic steps in committed cells. We have observed that PKB/Akt activity is inhibited by ddFSK, but a constitutive active form of the enzyme cannot counteract any of the inhibitory effects of the drug on cell energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it enhances glucose uptake by stimulating the expression of the plasma membrane glucose transporter Glut-1, 18 and it mediates the activation of 6-phosphofructo-2-kinase 19 and hexokinase. 20 Thus, PKB/Akt activation may favor cell survival, 21,22 or alternatively it may support execution of the final apoptotic steps in committed cells. We have observed that PKB/Akt activity is inhibited by ddFSK, but a constitutive active form of the enzyme cannot counteract any of the inhibitory effects of the drug on cell energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…21 The hallmark of PKB/ Akt activation is the phosphorylation at the Thr308/Ser473 residues. As reported in Figure 10a, the phosphorylation of Ser473-Akt was abolished by ddFSK treatment independently of apoptosis induction.…”
Section: Bcl-x L or Pkb/akt Overexpression Do Not Change The Effects mentioning
confidence: 99%
See 1 more Smart Citation
“…This inhibition of phosphorylation of serine residues also inhibits the interaction between BAD and BCL-XL, an antiapoptotic regulatory protein of the BH3 subfamily, resulting in BAD remaining in an active proapoptotic form. Reports have also suggested that ZD1839 decreases the phosphorylation of Akt via the phosphatidylinositol 3-kinase pathway resulting in decreased phosphorylation of BAD again resulting in an increase in the proportion of the active form of this regulatory protein (Kennedy et al, 1999). A combination of the proposed models or elements of the models may result in the loss of the fine balance of the EGFR signalling cascade, which protects against radiation-induced cell damage, thereby leading to increased cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Another survival pathway that protects mitochondrial integrity is the phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway (Kennedy et al, 1999). To see if Akt signaling is affected, we tested how ARC may modulate this pathway in NB-1691 cells.…”
Section: Targeting Akt In Neuroblastoma Cells Sk Radhakrishnan Et Almentioning
confidence: 99%